Effect of certolizumab pegol over 96 weeks of treatment on inflammation of the spine and sacroiliac joints, as measured by MRI, and the association between clinical and MRI outcomes in patients with axial spondyloarthritis. Issue 1 (24th April 2017) - Braun, Jürgen; Baraliakos, Xenofon; Hermann, Kay-Geert; Landewé, Robert; Machado, Pedro M; Maksymowych, Walter P; Davies, Owen; Hoepken, Bengt; Nurminen, Tommi; Stach, Christian; van der Heijde, Désirée
Abstract : Objective: To report MRI outcomes and explore the relationship between clinical remission and MRI inflammation in patients with axial spondyloarthritis (axSpA) from the RAPID-axSpA trial, including radiographic (r-)axSpA and non-radiographic (nr-)axSpA. Methods: RAPID-axSpA (NCT01087762 ) was double-blind and placebo-controlled to week 24, dose-blind to week 48 and open-label to week 204. Patients were randomised to certolizumab pegol (CZP) or placebo. Placebo patients entering dose-blind were rerandomised to CZP. MRIs performed at baseline, weeks 12, 48 and 96 were scored by 2 reviewers independently: Spondyloarthritis Research Consortium of Canada (SPARCC) for sacroiliac (SI) joints; Berlin modification of the Ankylosing Spondylitis spine MRI scoring system for disease activity (Berlin) for spine. Inflammation thresholds: SPARCC≥2; Berlin>2. Remission thresholds: SPARCC<2 (SI joints); Berlin≤2 (spine); Ankylosing Spondylitis Disease Activity Score (ASDAS) inactive disease (<1.3, clinical). Results: Across 163 patients in the MRI set (109 CZP; 54 placebo), week 12 mean changes from baseline in MRI scores were greater for CZP versus placebo: SPARCC: −4.8 (SD 8.6) vs −1.6 (7.8; p<0.001); Berlin: −2.9 (4.2) vs 0.2 (4.8; p<0.001). Improvements were maintained to week 96. Week 12 MRI remission was achieved by 52.6% of patients with baseline MRI inflammation in SI joints, 62.0% in the spine and 37.9% of patients with both. MRI remission rates were sustained to week 96, with similar trends in r-axSpA and nr-axSpA. At week 96, 57.5% vs 65.9% of patients achieving versus not achieving clinical remission had MRI remission. Conclusions: CZP reduced inflammation in the spine and SI joints in patients with r-axSpA and nr-axSpA, with improvements maintained over 96 weeks. Substantial proportions of patients achieved MRI remission. Concordance between clinical remission and current definitions of absence of MRI inflammation was limited. Trial registration number: NCT01087762 ; Post-results.